Stem Bark Extract and Fraction of Persea americana (Mill.) Exhibits Bactericidal Activities against Strains of Bacillus cereus Associated with Food Poisoning - Akinpelu, David; Aiyegoro, Olayinka Ayobami; Akinpelu, F. Oluseun; Okoh, I. Anthony (journal of molecules, 2020)
international journal of molecules, 55. p. 422-6